2014
DOI: 10.5999/aps.2014.41.4.344
|View full text |Cite
|
Sign up to set email alerts
|

Platybasia in 22q11.2 Deletion Syndrome Is Not Correlated with Speech Resonance

Abstract: BackgroundAn abnormally obtuse cranial base angle, also known as platybasia, is a common finding in patients with 22q11.2 deletion syndrome (22q11DS). Platybasia increases the depth of the velopharynx and is therefore postulated to contribute to velopharyngeal dysfunction. Our objective was to determine the clinical significance of platybasia in 22q11DS by exploring the relationship between cranial base angles and speech resonance.MethodsIn this retrospective chart review at a tertiary hospital, 24 children (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Differences in the cranial base angles are visualized in Figure 2. Using an anterior cranial base angle greater than 136° to define platybasia (similar to methods used by Spruijt et al, 2014), we found that 5 of the 13 participants (38%) had platybasia. This is below the reported incidence of platybasia in individuals with 22q11DS, possibly due to the exclusion of individuals with cleft palate in the group with 22q11DS in the present study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Differences in the cranial base angles are visualized in Figure 2. Using an anterior cranial base angle greater than 136° to define platybasia (similar to methods used by Spruijt et al, 2014), we found that 5 of the 13 participants (38%) had platybasia. This is below the reported incidence of platybasia in individuals with 22q11DS, possibly due to the exclusion of individuals with cleft palate in the group with 22q11DS in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…This is below the reported incidence of platybasia in individuals with 22q11DS, possibly due to the exclusion of individuals with cleft palate in the group with 22q11DS in the present study. Nachmani et al (2013) reported 50% of their participants presented with platybasia while Spruijt et al (2014) reported platybasia in 67% of their participants. Platybasia, although a common characteristic in 22q11DS, is not always present.…”
Section: Discussionmentioning
confidence: 99%